2010
DOI: 10.1177/104063871002200223
|View full text |Cite
|
Sign up to set email alerts
|

Non–West Nile virus-Associated Mortality in a Population of American Crows (Corvus Brachyrhynchos): A Gross and Histopathologic Study

Abstract: The American crow (Corvus brachyrhynchos) is a common urban and rural inhabitant of the Northeast and Midwest United States that is commonly infected with West Nile virus (WNV). The current study was initiated to determine non-WNV-associated causes of mortality in the American crow. All animals (40/40) tested negative for WNV infection via polymerase chain reaction and had no evidence of infection based on immunohistochemistry. Common gross necropsy findings included external trauma (6/40), hepatosplenomegaly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In winter, crows aggregate in large nocturnal roosts (sometimes .10,000 birds; Hinton et al 2015), often in areas of high human density and activity (Gorenzel and Salmon 1995, Hinton et al 2015. Crows are of particular concern with respect to disease transmission because they are common urban and suburban birds in North America (McGowan 2001) that can harbor numerous pathogens important to humans, domestic animals, and wildlife, including West Nile virus (Wheeler et al 2014, Hinton et al 2015, Campylobacter jejuni (Weis et al 2016, Taff and, and other pathogens (Miller et al 2010, Halová et al 2014, Freund et al 2016, Jamborova et al 2017, Townsend et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In winter, crows aggregate in large nocturnal roosts (sometimes .10,000 birds; Hinton et al 2015), often in areas of high human density and activity (Gorenzel and Salmon 1995, Hinton et al 2015. Crows are of particular concern with respect to disease transmission because they are common urban and suburban birds in North America (McGowan 2001) that can harbor numerous pathogens important to humans, domestic animals, and wildlife, including West Nile virus (Wheeler et al 2014, Hinton et al 2015, Campylobacter jejuni (Weis et al 2016, Taff and, and other pathogens (Miller et al 2010, Halová et al 2014, Freund et al 2016, Jamborova et al 2017, Townsend et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we assumed that the two sympatric species (carrion crows and jungle crows), which have similar habitats and co-occur in east Asia, likely share a more similar suite of pathogens with each other than with American crows. Diverse pathogen burdens are well-documented in all three species, and a comparative study of jungle crows and carrion crows revealed that ten specific helminth species were shared between the two species ( Mizuno, 1984 ; Miller et al, 2010 ; Wheeler et al, 2014 ). There have been several surveys of intestinal parasites in American crows; however no report to date has identified these Asian helminth species in American crows, except for one anecdotal case ( Jones, 1968 ; Hendricks, Harkema & Miller, 1969 ; Cawthorn, Anderson & Barker, 1980 ; Naderman & Pence, 1980 ; Mizuno, 1984 ; Miller et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse pathogen burdens are well-documented in all three species, and a comparative study of jungle crows and carrion crows revealed that ten specific helminth species were shared between the two species ( Mizuno, 1984 ; Miller et al, 2010 ; Wheeler et al, 2014 ). There have been several surveys of intestinal parasites in American crows; however no report to date has identified these Asian helminth species in American crows, except for one anecdotal case ( Jones, 1968 ; Hendricks, Harkema & Miller, 1969 ; Cawthorn, Anderson & Barker, 1980 ; Naderman & Pence, 1980 ; Mizuno, 1984 ; Miller et al, 2010 ). A strong relationship between MHC class IIB and resistance to helminth parasites has been established ( Goüy de Bellocq, Charbonnel & Morand, 2008 ; Zhang & He, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem examinations were performed on the dead crows discovered between November 2006 and July 2008 that tested negative for West Nile virus (WNV), as described in Miller et al (2010) and Townsend et al (2009a). Of the 299 focal birds, 100 were still alive, 21 died with signs of infectious disease (poxviral dermatitis, n ¼ 14; WNV, n ¼ 3; bacterial infections, n ¼ 2; fungal pneumonia, n ¼ 1; enteritis; n ¼ 1), 54 met with traumatic deaths and 124 died or disappeared of unknown causes by July 2008 (described in detail in Townsend et al 2009a).…”
Section: Introductionmentioning
confidence: 99%